Institutional Effects on the Evolution of the Size Distribution of Firms - Magnus Henrekson; Dan Johansson (The Research Institute of Industrial Economics (IUI), 1998)
In this paper it is argued that the size distribution of firms may largely be determined by institutional factors. This hypothesis is tested in an exploratory fashion by studying the evolution of the size distribution of firms over time in Sweden for a period spanning from the late 1960s to the early 1990s. The data used is divided into finer size classes compared to most previous studies. This gives more scope for investigating the impact of institutions. Moreover, we use a unique data set, starting in 1984, to take account of corporate groups and government ownership. The analysis shows a poor development for intermediate-sized (10-199 employees) firms. This is likely to reflect the existence of a threshold that many firms are either unwilling or unable to cross. The analysis of the institutions and rules of the game determining the entrepreneurial and business conditions in Sweden indicate that the conditions have been unfavorable for small firms, and hence that too few small firms have managed to grow out of the smallest size classes. The conclusion is supported by an international comparison of the number of firms in different size classes. Data indicate that Sweden has fewer small (10-99) employees), and more large (500+) firms per capita than other European countries.
Keywords: H30; J21; L52; 330; Business taxation; Industrial policy; Industrial structure; Size distribution; Betriebsgrößenstruktur; Industriepolitik; Schweden